Mycetozoan incidence in soils and their potential for ecosystem quality assessment - Guyer, Hannah Elizabeth (2017)
Two experiments employing a modified version of the standard “Cavender Method” were used to evaluate the incidence patterns of myxomycete and dictyostelids associated with different soils collected across north and central America. The soils were subjected to variable culturing conditions and parameters including plant material quality, agar type and bacterial food source. Ecological variables such as geographic location and land use quality were also evaluated to determine potential differences affecting the soils. The study also aimed to document the potential for mycetozoans to serve as indicators of ecosystem quality. The results indicated that plant materials with middle hardness and moderate cellulose to lignin ratio, in conjunction with an intermediate rich culturing media favoured the growth of mycetozoans. Also, Bacillus subtilis represented a suitable alternative to Escherichia coli. Dictyostelids were more commonly recovered from tropical soils than temperate soils, while the opposite pattern was observed for myxomycetes. No differences in mycetozoan incidence were detected when landscape-scale and soil quality parameters were examined. Overall, data related to the utility of using mycetozoans as bioindicators are still limited, but the results of this study suggest that more targeted, scaledependent studies are warranted. The modified protocol used herein appears to represent a reliable method to generate consistent data for ecological studies of mycetozoans, particularly when tropical soils are used.